Nonautistic Motor Stereotypies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Clinical features and long-term outcomes of 100 children (62 boys and 35 girls) with motor stereotypies were evaluated by review of records and telephone interviews at Johns Hopkins Hospital, Baltimore, MD.